2021
DOI: 10.3389/fanim.2021.761930
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Diversity Along the Farm-to-Fork Continuum of Pastured Poultry Flocks in the Southeastern United States

Abstract: Greater consumer demand for all natural, antibiotic-free poultry products has led to an increase in pastured poultry operations. Given the increased level of environmental interaction, and the potential increase in exposure to foodborne pathogens, a greater understanding of the prevalence and diversity of Salmonella populations inherent within pastured poultry flocks. To achieve this, 42 pastured poultry flocks from 11 farms were sampled using a farm-to-fork strategy and Salmonella was isolated and characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
1
7
1
Order By: Relevance
“…The results of this study are also higher than those reported in the European Union (EU) (Finland and Sweden: <1%; Ireland: 19.8%), Asia (China: 12.6%; Korea: 15.3%), and South America (Columbia: 17.8%) [ 35 38 ]. Studies done in the USA and India along the farm-to-fork pathway reported an overall lower prevalence of 18.1% and 25.8%, respectively, than that in the current study [ 39 , 40 ]. The proportion of Salmonella isolated from poultry can be influenced and varies by geographical location, environmental contamination, nature of farm management systems, type of production systems, breed of the flock, age of birds, sample size, sampling procedures, and the methods used for isolation [ 6 , 11 ].…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…The results of this study are also higher than those reported in the European Union (EU) (Finland and Sweden: <1%; Ireland: 19.8%), Asia (China: 12.6%; Korea: 15.3%), and South America (Columbia: 17.8%) [ 35 38 ]. Studies done in the USA and India along the farm-to-fork pathway reported an overall lower prevalence of 18.1% and 25.8%, respectively, than that in the current study [ 39 , 40 ]. The proportion of Salmonella isolated from poultry can be influenced and varies by geographical location, environmental contamination, nature of farm management systems, type of production systems, breed of the flock, age of birds, sample size, sampling procedures, and the methods used for isolation [ 6 , 11 ].…”
Section: Discussioncontrasting
confidence: 83%
“…A similar resistance phenotype was reported in Saudi Arabia, where clinical and environmental samples showed resistance to cefuroxime (90.9%) and cefoxitin (87.9%), while most isolates were susceptible to β -lactams [ 49 ]. Previous studies in Africa, Australia, and the USA have reported a higher frequency of resistance to cefuroxime or cefoxitin among Salmonella -positive poultry isolates [ 14 , 39 , 46 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, continuous variables did not meet the assumption of a normal distribution; therefore, non-parametric testing for direct comparisons was performed using Wilcoxon rank sum and signed rank tests, and the Kruskal-Wallis rank sum test was used for one-way analysis of variance tests. Additionally, a generalized linear model with a binomial distributed outcome and a log link function was performed as described earlier [66] to determine if there are significant differences in Salmonella prevalence (presence/absence) and the litter used for raising broiler chicks. The significance of the model was established using a likelihood ratio test (R function ANOVA with argument test set to “Chisq”).…”
Section: Methodsmentioning
confidence: 99%